2020
DOI: 10.1002/ppul.24673
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and responding to stress related to pulmonary function testing in cystic fibrosis through quality improvement

Abstract: Background Pulmonary function tests (PFTs) are performed routinely to evaluate lung function in patients with cystic fibrosis (CF). Staff at the Cincinnati Children's Hospital Medical Center CF Center observed stress in patients before PFTs. An interdisciplinary quality improvement (QI) team was assembled to address this clinical issue. Methods The Plan‐Do‐Study‐Act method of QI was used to investigate feasibility of assessing stress and offering brief interventions to reduce stress before PFTs. Interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Two additional studies reported related outcomes. 87,88 Sleep quality. Six studies reported data on caregiver sleep quality.…”
Section: Humanistic Caregiver Burdenmentioning
confidence: 99%
“…Two additional studies reported related outcomes. 87,88 Sleep quality. Six studies reported data on caregiver sleep quality.…”
Section: Humanistic Caregiver Burdenmentioning
confidence: 99%
“…1 Additionally, individuals with CF frequently face anxiety from healthcare experiences and procedures. 12 13 Illness-specific anxiety is associated with impaired functioning, emotional distress and lower quality of life. 14…”
Section: Introduction Background and Knowledgementioning
confidence: 99%
“…The Pediatric CF Center at Cincinnati Children's Hospital is a quaternary care center located in the Midwest caring for approximately 250 individuals with CF. Cincinnati Children's Hospital is a leader in healthcare QI, and the CF Center has significant experience implementing multi‐disciplinary QI projects to advance clinical outcomes 21–26 . Additionally, the CF Center participates in the CF Learning Network, a multi‐site collaborative supported by the CF Foundation that uses QI methodology to improve patient outcomes for the CF community.…”
Section: Methodsmentioning
confidence: 99%